Agrarian Socialism: The Cooperative Commonwealth Federation in Saskatchewan: A Study in Political Sociology - Lipset, Seymour Martin (Anchor books, 1968)
The Cooperative Commonwealth Federation government in Saskatchewan, which was elected in 1944, remains the only government with avowed socialist goals to have come to power in Canada or the United States. In 1949, Seymour Martin Lipset wrote Agrarian Socialism, which has since become a classic, a study of the social background that enabled the movement to succeed in the region that it did. The CCF government, however, remained in power for twenty years. So this new Anchor edition contains not only a new introduction by the author, evaluating his earlier research in terms of later developments, but five new chapters by other sociologists who, taking off from the findings in Agrarian Socialism, studied later developments in Saskatchewan.... -- Publisher's description
Keywords: Co-operative Commonwealth Federation. Saskatchewan; Political Science(General); Politics and government; Politieke wetenschappen (algemeen); Saskatchewan; Saskatchewan Politics and government; Socialism; Socialism Saskatchewan; agricultural policy; agriculture; canada; landbouw; landbouwbeleid; politics; politiek; saskatchewan; socialism; socialisme; sociologie; sociology